PREVENTION OF INJURY DURING TRAINING AND COMPETITION - Dr.Daisy Rani (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Sports injuries are injuries that occur in athletic activities or exercising. They can result from accidents, poor training, and technique in practices, inadequate equipment and overuse of a particular body part. The highest incident is seen in adolescent playing pivoting sports such as football, basketball and team handball and the incidence is 3-5 times higher in women then man. However lower back injuries are also common (12%) Especially in jumps, throw's and combined events several risk factors for developing running related injuries have been investigated and can be roughly divided into intrinsic (e.g. cognitive properties) and extrinsic (e.g. ground surface, footwear and training load). It is very important for all coaches, trainers, physical educationist and player to know the causes symptoms treatment and prevention of sports injuries in order to avoid most of these types of injuries also to update the poor training methods.